Evaluating effectiveness of self-help groups in reduction of stigma in patients with neglected tropical diseases in Southern Nigeria: A cluster randomised study - Chinwe C. Eze; Ngozi Ekeke; Wim van Brakel; Edmund Ndudi Ossai; Precious Henry; Amaka Onyima-Esmai; Charles C. Nwafor; Ngozi Murphy-Okpala; Anthony Meka; Okechukwu Ezeakile; Martin Njoku; Francis S. Iyama; et al. (PLoS ONE, 2025)
Introduction Neglected tropical diseases (NTDs), notably leprosy and Buruli ulcer (BU), often lead to visible impairments and disabilities. Consequently, individuals affected by these conditions face stigmatization, discrimination, and mental health disorders. Stigma is particularly prevalent in leprosy, affecting self-esteem, social participation, self-efficacy, and overall quality of life. Various interventions have been developed to mitigate leprosy-related stigma, including individual and group counseling, peer support, economic empowerment initiatives, and establishment of self-help groups. However, rigorous evaluation of the various interventions through randomized controlled trials is lacking, especially within the Nigerian context, and none has included persons affected by BU. To address this gap, effectiveness of combined leprosy and BU self-help groups (SHGs) on stigma reduction was assessed as part of a larger randomized controlled study. Methodology/principal findings A cluster randomized study was conducted in Southern Nigeria from 2021 to 2023. Five local government areas (LGAs) were selected for each of the intervention and control arms. People affected by leprosy or BU were organized into SHGs in the intervention LGAs. Control LGAs were maintained on the existing standard of care, which did not include SHGs. Monthly peer-support meetings were held for 24 months following standardized guidelines after appropriate training of SHG members. The intervention targeted perceived and experienced stigma. Pre- and post-intervention stigma assessments were conducted using the stigma assessment and reduction of impact (SARI) scale in both intervention and control LGAs. A total of 635 persons affected by leprosy or BU were recruited—362 in the intervention group and 273 in the control group. At baseline, respondents in the intervention group had a significantly higher adjusted mean total score on the SARI Stigma Scale compared to the control group, with an adjusted mean difference of 10.75 (95% CI: 8.05–13.46, p < 0.000). However, post-intervention, the adjusted mean SARI Stigma Score significantly decreased in the intervention group compared to the control group, with an adjusted mean difference of 37.72 (95% CI: 36.01–39.43, p < 0.000). Conclusion/significance Peer-support and psychosocial support through SHGs significantly contributed to stigma reduction among persons affected by Leprosy/BU. SHGs can play a key role in stigma reduction interventions within NTD programs, contributing to the global leprosy target of achieving zero stigma and discrimination. Trial Registration: ISRCTN Registry: ISRCTN 83649248. https://trialsearch.who.int/Trial2.aspx? TrialID = ISRCTN83649248.